Non-hormonal mediators of uterine fibroid growth. - Cetin, Esra (Curr Opin Obstet Gynecol, 2020)
PURPOSE OF THE REVIEW: Uterine fibroids (UFs) are the most common benign neoplasms of the female reproductive tract and one of the major public health concerns. Although most women with UFs are asymptomatic, over 30% of them will present with varying symptoms. This review focuses on the role of non-hormonal mediators and pathways in UF biology. Furthermore, it provides data regarding the most recent findings in the field of compounds which use those non-hormonal pathways in the medical therapy of UFs. RECENT FINDINGS: Complex signaling pathway alterations are crucial for UF development. The topic of the pathophysiology of UFs focuses mostly on steroids and other hormones. However, other very important pathways exist which are independent of hormones. Some of the most important pathways which are non-hormonal, but in some cases still hormone-depended, include growth factors, cytokines and inflammation, Smad proteins, wingless type/β-catenin and others. SUMMARY: Much more is known about hormonal than about non-hormonal signaling in UFs. Growth factors, early life exposure and inflammation are key factors in UF biology. Numerous agents depend on those pathways and may find their place in the current and future therapy of UFs.